Influencing factors on bread-derived exposure to ochratoxin A: type, origin and composition - Duarte, S. C. (2013)
The nearly ubiquitous consumption of cereals all over the world renders them an important position in international nutrition, but concurrently allocates exposure to possible contained contaminants. Mycotoxins are natural food contaminants, difficult to predict, evade, and reduce, so it is important to establish the real contribution of each contaminated food product, with the aim to evaluate mycotoxin exposure. This was the key objective of this survey and analysis for ochratoxin A content on 274 samples of commercialized bread in the Portuguese market, during the winter 2007. Different bread products were analyzed through an HPLC-FD method, including traditional types, novel segments, and different grain based bread products. A wide-ranging low level contamination was observed in all regions and types of bread products analyzed, especially in the Porto and Coimbra regions, and in the maize and whole-grain or fiber-enriched bread. Nevertheless, the exposure through contaminated wheat bread continues to be the most significant, given its high consumption and dominance in relation to the other types of bread.